Local Administrative Organization and Enhancing Healthcare Services for Senior and Dependent People through Digital Technology: A Case Study of Wiang Yong Subdistrict Municipality, Muang District, Lamphun Province - Srimanee, Chawis; Homhuan, Sakda; Siriphon, Aranya; Boonchieng, Waraporn; Nethngam, Siraseth; Kattirat, Witavas (Connexion: Journal of Humanities and Social Sciences, 2024)
This research article examines the role of local administrative organizations (LAOs) in delivering healthcare services to vulnerable groups within local communities, particularly the elderly and individuals with dependency conditions. The study focuses on Wiang Yong Subdistrict, Lamphun Province, as a case study, to develop effective healthcare service mechanisms through the application of digital technology and the capacity building of local staff. The objective of study is to design an operational system and apply appropriate digital technologies to enhance service delivery. Using an action research approach, the study engaged local staff and partnering network from the outset, employing a “co-creation” methodology. This approach began with identifying community needs and was supported by multidisciplinary academic knowledge to develop practical and concrete solutions. Digital technology served as a key tool in driving healthcare service delivery in the area. The findings revealed the development of two innovative applications: (1) the “Hub Song Hong Ya” system (MedCarHub), which facilitates medical transportation services for scheduled appointments, and (2) the Medical Prosthesis Borrow-Return system, which manages the borrowing and returning of medical equipment. These digital innovations not only leverage technology but also integrate it into the operational processes of LAOs, significantly enhancing the efficiency of healthcare service delivery. The innovations have effectively reduced travel costs, medical equipment expenses, and awaiting times by 100% for vulnerable groups in the subdistrict. This has alleviated key challenges faced by LAOs in providing healthcare services, particularly for the elderly and dependent people in non-emergency situations, where appropriate support systems are often lacking. Furthermore, the research has enabled Wiang Yong Subdistrict Municipality to serve as a model for local innovation development. Local innovators have gained the capacity to transfer their knowledge and experiences to other LAOs in the future, thus fostering broader adoption of these innovations across local administrative organizations.